Development of [I(ads)|Au(pc)] electrode to attain electrocatalytic oxidation of paracetamol: An efficient platform for quantitative analysis. Issue 4 (August 2022) - Hoq, Jahidul; Islam, Md. Fahamidul; Miah, Md. Rezwan; Rahman, Mohammed M.; Almahri, Albandary; Hasnat, Mohammad A.
Abstract: Electrochemical oxidation of paracetamol (PCT) has exclusively been investigated using polycrystalline gold electrode modified with iodine adlayer [I(ads) |Au(pc)] in alkaline medium. Irreversible adsorption of PCT makes Au(pc) surface unfeasible for studying PCT oxidation reaction. This limitation of Au(pc) surface could be eliminated simply by iodide (I - ) adsorption. It was noticed that the spontaneous I - adsorption blocks PCT adsorption sites on Au(pc) surface, which additionally improves PCT oxidation reaction by increasing electron transfer rate. Iodine adlayer (I-adlayer) formulated electrode facilitated PCT electro-oxidation via an alternative diffusion-controlled pathway with an anodic electron transfer coefficient ( β ) of 0.47 and heterogeneous rate constant ( k o ) of 0.0911 cm s −1 where an electron transfer step determines the reaction rate. The sensing experiments revealed that the [I(ads) |Au(pc)] electrode attained linear dynamic range from 4.5 to 1600 μM of PCT. The obtained sensitivity and limit of detection (LOD) of the [I(ads) |Au(pc)] electrode surface was determined to be 8.37( ± 1.6)× 10 −4 mA cm −2 μM −1 and 0.65 ± 0.02 μM, respectively. The formulated [I(ads) |Au(pc)] catalyst was applied to quantify the relative PCT percentage in commercial tablets using batch injection analysis supported by chronoamperometry. Obtained relative percentage closely matched with the corresponding analysis performed with Raman spectroscopy. Therefore, developed I-adlayer coated Au(pc) electrode is analytically robust and validated for routine analysis of PCT concentration in relevant pharmaceutical applications. Graphical Abstract: ga1 Highlights: Adsorption of paracetamol (PCT) on polycrystalline Au surface made it unfeasible for PCT electro-oxidation reaction. Iodine adlayer improved the electron transfer rate by protecting the Au electrode from fouling in PCT electro-oxidation. Iodine adlayer on Au surface converted the adsorption-controlled process into a mass transfer-controlled process. Relative PCT percentage in commercial tablets was accurately quantified by means of [I(ads) |Au(pc)] electrode.